2019
DOI: 10.1002/jpen.1727
|View full text |Cite
|
Sign up to set email alerts
|

Volume‐Based Feeding Enhances Enteral Delivery by Maximizing the Optimal Rate of Enteral Feeding (FEED MORE)

Abstract: BackgroundThe importance of enteral nutrition (EN) in critically ill patients is well documented. However, actual administration of EN frequently does not amount to prescribed nutrition goals. Persistent underfeeding may lead to impaired immune response, increased mortality, and higher costs. Traditionally, EN uses a rate‐based approach, utilizing slow titration to goal and a final fixed hourly rate, regardless of interruptions in feeding. Volume‐based feeding (VBF) establishes a 24‐hour EN goal volume, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…Volume-based feeding protocols have previously shown to be an effective solution to compensate for excess EN holds that are common in ICU settings; however, these more aggressive EN protocols have not been studied in cardiac surgery populations and are more appropriate for hemodynamically stable patients with a low risk of GI intolerance. 65 These protocols allow the RN to adjust the EN rate to maximize the total 24-h volume delivered, which may result in higher EN delivery rates (ie, 100-150 ml/h). These high EN rates may be poorly tolerated in the first postoperative week for cardiac surgery patients in the setting of hemodynamic instability and risk factors for bowel ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Volume-based feeding protocols have previously shown to be an effective solution to compensate for excess EN holds that are common in ICU settings; however, these more aggressive EN protocols have not been studied in cardiac surgery populations and are more appropriate for hemodynamically stable patients with a low risk of GI intolerance. 65 These protocols allow the RN to adjust the EN rate to maximize the total 24-h volume delivered, which may result in higher EN delivery rates (ie, 100-150 ml/h). These high EN rates may be poorly tolerated in the first postoperative week for cardiac surgery patients in the setting of hemodynamic instability and risk factors for bowel ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 An alternative is to use a volume based approach to target a total 24 hour volume of enteral nutrition, which is a good strategy to both rapidly achieve goal as well as counteract the impact of interruptions on overall nutrition intake. [48][49][50] A volume based strategy, combined with a nurse directed nutrition educational intervention has been shown to increase protein and calorie delivery in medical and surgical critical care populations, and should be adopted as the optimal method by which to provide nutrition in a critically ill SAH patient population. 51 There are several limitations to this study that warrant further discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Brierley‐Hobson and colleagues 15 reported no difference in the amount of insulin prescribed between patients receiving VBF and RBF but did note higher morning blood glucose levels in the VBF group. Similarly, Holyk et al 16 reported no difference in average blood glucose levels between VBF and RBF but noted an increased incidence of moderate hyperglycemia during catch‐up periods compared with non–catch‐up periods in the same patients. One study reported a decreased occurrence of hyperglycemia and hypoglycemia in the VBF cohort, 17 and another found no difference in hyperglycemia and glycemic variance between groups 18 …”
Section: What Are the Indications And Strategies To Use For “Catch‐up...mentioning
confidence: 90%